2011
DOI: 10.1590/s0100-879x2011000700010
|View full text |Cite
|
Sign up to set email alerts
|

Aging alters the production of iNOS, arginase and cytokines in murine macrophages

Abstract: The limited amount of information on the primary age-related deficiencies in the innate immune system led us to study the production of inducible nitric oxide synthase (iNOS), arginase, and cytokines in macrophages of young (8 weeks old) and old (72 weeks old) female BALB/c mice. We first evaluated iNOS and arginase inducers on peritoneal (PMΦ) and bone marrow-derived (BMMΦ) macrophages of young BALB/c and C57BL/6 mice, and then investigated their effects on macrophages of old mice. Upon stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 9 publications
4
14
0
Order By: Relevance
“…However, the animal’s age modulated this response, as aged mice showed increased hippocampal expression of Arg1, CD206, SOCS1, and Ym1 in response to IL-4/IL-13 administration relative to adults. These data are in agreement with prior work showing that macrophages from aged mice show increased Arg1 expression in response to IL-4 administration (Cecilio et al, 2011). Similarly, Kumar et al (2013) report that twenty-four hours following a traumatic brain injury (TBI) aged mice showed increased expression of the M2a-associated genes Arg1, Ym1, and CD206 relative to adult mice.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the animal’s age modulated this response, as aged mice showed increased hippocampal expression of Arg1, CD206, SOCS1, and Ym1 in response to IL-4/IL-13 administration relative to adults. These data are in agreement with prior work showing that macrophages from aged mice show increased Arg1 expression in response to IL-4 administration (Cecilio et al, 2011). Similarly, Kumar et al (2013) report that twenty-four hours following a traumatic brain injury (TBI) aged mice showed increased expression of the M2a-associated genes Arg1, Ym1, and CD206 relative to adult mice.…”
Section: Discussionsupporting
confidence: 93%
“…However, less is known about how aging affects the induction of an anti-inflammatory M2 response. The present data confirm that infusion of the anti-inflammatory cytokines IL-4 and IL-13 induces expression of the M2-associated genes, namely, Arg1, Fizz1, CD206, SOCS1, Ym1, TGF-β, and IL-1ra (Butovsky et al, 2005, Cecilio et al, 2011, Pepe et al, 2014). However, the animal’s age modulated this response, as aged mice showed increased hippocampal expression of Arg1, CD206, SOCS1, and Ym1 in response to IL-4/IL-13 administration relative to adults.…”
Section: Discussionsupporting
confidence: 84%
“…Many studies have been demonstrated the impact of immunesenescence or age-related immune cell deficiency in MØ functions [9][14]. For example, aging impairs production of NO [14] and phagocytic capacity [9], [10], [12] of MØ and reduces their expression of MHC class II [13].…”
Section: Discussionmentioning
confidence: 99%
“…The maturation state influences the functional behavior of MØ; their performance is particularly compromised as they age [9][14]. Age-related debilitation is reflected in activities associated with MØ microbicidal function, including impairment in phagocytic ability and in the production of inflammatory cytokines, chemokines and free radicals; additionally, expression of MHCII molecules is diminished, which may contribute to poor CD4 + T cell responses.…”
Section: Introductionmentioning
confidence: 99%
“…The main reported age-related changes in macrophage functioning include decreased response to pathogens and increased basal expression of pro-inflammatory cytokines [27], which contributes greatly to the general inflammatory phenotype that is observed during aging; decreased killing of intracellular pathogens and decreased capture of antigens [28]; and changes in expression of effector's molecules [29]. Birjandi and colleagues [30] suggests that the splenic structural arrangement undergoes disorganization and negative functional changes occur in several macrophage populations.…”
mentioning
confidence: 99%